Electrodes based on nafion and epoxy-graphene composites for improving the performance and durability of open cathode fuel cells, prepared by electrospray deposition. (5th April 2022) - Gómez, M.A.; Navarro, A.J.; Giner-Casares, J.J.; Cano, M.; Fernández-Romero, A.J.; López-Cascales, J.J.
Abstract: Fabrication of electrodes for polymer electrolyte fuel cells is a intriguing process in which a balance between gas transport, electrical conductivity, proton transport and water managing must be optimized. In this work four different electrodes prepared by electrospray deposition have been studied using different catalytic inks, in which Nafion and epoxy doped with Graphene-Nanoplatelets were used as binders. After studying the behavior of those electrodes in a single open cathode fuel cell proton electrolyte membrane, it is clear that the addition of epoxy as binder doped with graphene, improves the performance of the fuel cell and increase the mechanical stability of the electrode avoiding the loose of catalyst during the electrode manipulation in the fuel cell assembly process and the durability of the fuel cell. To explain this behavior, an ex-situ study was carried out, in which properties such as its surface morphology, hydrophobicity and electrical and thermal conductivity of those electrodes were studied. From the results of this study, such improvement in the performance of the fuel cell was justified on the basis of the increase in the electrical conductivity, a diminution in its thermal conductivity and an enhancement of hydrophobicity (surface morphology) of the deposited catalyst layer, when an optimum quantity of epoxy is added to the catalytic ink that makes to improve the mechanical properties of those electrodes. Highlights: The electrospray technique allows the fabrication of nanostructured electrodes for its use in fuel cells. The addition of epoxy/graphene to the catalytic ink improves the performance of the fuel cells. The presence of epoxy/graphene improves the adherence of the catalyst to the proton membrane.